Effects of loading a magnetic field longitudinal to the linear particle-beam track on yields of reactive oxygen species in water. (4th May 2021) - Matsumoto, Ken-ichiro; Nakanishi, Ikuo; Abe, Yasushi; Sato, Shinji; Kohno, Ryosuke; Sakata, Dousatsu; Mizushima, Kota; Lee, Sung Hyun; Inaniwa, Taku
Abstract: The effects of a magnetic field longitudinal to the ion beam track on the generation of hydroxyl radicals (OH) and hydrogen peroxide (H2 O2 ) in water were investigated. A longitudinal magnetic field was reported to enhance the biological effects of the ion beam. However, the mechanism of the increased cell death by a longitudinal magnetic field has not been clarified. The local density of OH generation was estimated by a method based on the EPR spin-trapping. A series of reaction mixtures containing varying concentrations (0.76‒2278 mM) of DMPO was irradiated by 16 Gy of carbon- or iron-ion beams at the Heavy-Ion Medical Accelerator in Chiba (HIMAC, NIRS/QST, Chiba, Japan) with or without a longitudinal magnetic field (0.0, 0.3, or 0.6 T). The DMPO-OH yield in the sample solutions was measured by X-band EPR and plotted versus DMPO density. O2 -dependent and O2 -independent H2 O2 yields were measured. An aliquot of ultra-pure water was irradiated by carbon-ion beams with or without a longitudinal magnetic field. Irradiation experiments were performed under air or hypoxic conditions. H2 O2 generation in irradiated water samples was quantified by an EPR spin-trapping, which measures OH synthesized from H2 O2 by UVB irradiation. Relatively sparse OH generation caused by particle beams in water were not affected by loading a magnetic field on the beam track. O2 -dependent H2 O2 generation decreased and oxygen-independent H2 O2 generation increased after loading a magnetic field parallel to the beam track. Loading a magnetic field to the beam track made OH generation denser or made dense OH more reactive.